Lipomatózní hamartomy mozku--malformace subarachnoidálního prostoru - Zámecník, J; Kyncl, M (Ceskoslovenska patologie, 2001)
Lipomatous hamartomas are rare disorders affecting the central nervous system. In our report, two observations of this disorder are presented. Both are interhemispheric in location and are associated with a complete agenesis of the corpus callosum, while having different histological structures. In our first patient, the intracranial formation caused refractory seizures, was partially surgically removed, and a biopsy was performed. Light microscopic examination disclosed the presence of a highly vascularized mature adipose tissue with numerous calcifications. The second case was an incidental finding at autopsy. Microscopically, we found adipose tissue together with numerous foci of hemopoiesis and structures of lamelar bone. In both cases, the indistinct demarcation of the collagenous capsule from the surrounding brain tissue and the continuity of the hamartoma with the leptomeninges were striking. In recent findings about the development of meninges and brain commissures, the origin of this disorder is explained as a defective resorption of the embryonic meninx primitiva. This disorder then causes other developmental aberrations of the brain, which are often found in association. The varying microscopic pattern of these disorders can also be satisfactorily explained by their origin in the primitive meninx, which is formed from both mesenchyme and neuroectoderm.
Keywords: Child; Hamartoma; Subarachnoid Space; subarachnoidální prostor; nádory mozku; Adult; dospělí; mozek; hamartom; Humans; mužské pohlaví; Male; lidé; lipom; Brain Neoplasms; Brain; dítě; Lipoma